2018
DOI: 10.1007/s10067-018-4076-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of PD-1 and Tim-3 expression on CD4+ T cells of patients with rheumatoid arthritis; negative association with DAS28

Abstract: Expression of T cell immunoglobulin and mucin-domain containing-3 (Tim-3) and programmed cell death-1 (PD-1) was studied on CD4 T cells of patients with rheumatoid arthritis (RA). Association of Tim-3 and PD-1 expression with disease activity of RA patients was also addressed. A total of 37 RA patients and 31 sex- and age-matched healthy controls were included in this study. Disease activity of RA patients was determined by Disease Activity Score of 28 joints scoring system (DAS28). A three-color flow cytometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 40 publications
2
17
0
Order By: Relevance
“…In agreement with our study, up‐regulation of Tim‐3 mRNA has been reported in both CD4 + and CD8 + T cells of CNS‐resident cells during EAE . In addition, we have also previously shown a significant elevation of PD‐1 and Tim‐3 on peripheral blood CD4 + T cells of patients with RA and asthma . Controversial findings have also been reported in systemic lupus erythematosus .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with our study, up‐regulation of Tim‐3 mRNA has been reported in both CD4 + and CD8 + T cells of CNS‐resident cells during EAE . In addition, we have also previously shown a significant elevation of PD‐1 and Tim‐3 on peripheral blood CD4 + T cells of patients with RA and asthma . Controversial findings have also been reported in systemic lupus erythematosus .…”
Section: Discussionsupporting
confidence: 92%
“…[23,38] In addition, we have also previously shown a significant elevation of PD-1 and Tim-3 on peripheral blood CD4 + T cells of patients with RA and asthma. [39,40] Controversial findings have also been reported in systemic lupus erythematosus. [41] To more explore the expression profile of PD-1 and Tim-3 immune checkpoints in CD8 + T cells, we also looked at the mRNA expression of these molecules in We found positive correlations between mRNA and protein expression of Tim-3 and PD-1 with disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…Much like transplantation, the management of autoimmune diseases frequently involves systemic immunosuppression, and the role of CD4 T-cells in autoimmune pathology has long been recognized (138,139). Conversely, a negative correlation between CD4 inhibitory receptor expression and disease severity has been observed in a rheumatoid arthritis (RA) population (140), although this has not been a consistent finding (141) (142)(143)(144). Additionally, persistent stimulation of CD4 T-cells with endogenous peptides resulted in loss of cytokine production and proliferation, upregulation of inhibitory markers, and delayed onset of autoimmune diabetes (145).…”
Section: Original Evidence: Chronic Infectionsmentioning
confidence: 99%
“… 22 , 53 Blocking TIM-3 increases the production of IFNγ by lymphocytes, but it is unclear as to what forms the molecular basis of this action. 54 In patients with gastric, colorectal, liver, and pancreatic cancers, TIM-3 tumor expression correlated with tumor invasion, reduced survival, and metastasis; thus, TIM-3 can be implicated in carcinogenesis. 55 …”
Section: Inhibitory Molecules Related To T-cell Dysfunction In Cancermentioning
confidence: 97%